The superpowers : a short history - Dukes, Paul, 1934-2021 (London ; New York : Routledge, 2000)
The Superpowers traces the development of the USA and Russia from 1898 to 2000, placing the cold war, from inception to ending, into the wider social, economic and political context.
Book Cover; Title; Contents; Preface; Inheritance: nations and empires, before 1898; Conception: the First World War and revolution, 1898 1921; Gestation: new world orders and the Second World War, 1921 45; Youth: Cold War and decolonisation, 1945 68; Maturity: Cold War and the Third World, 1968 91; The legacy: death or rebirth? 1991; Notes; Bibliography; Index.
Includes bibliographical references (pages 185-186) and index.
Print version record.
eBooks on EBSCOhost
Keywords: United States -- History; Russia (Federation) -- History; Soviet Union -- History; United States -- Foreign relations; Russia (Federation) -- Foreign relations; Soviet Union -- Foreign relations; Imperialism -- History; Cold War; United States -- History; États-Unis -- Histoire; URSS -- Histoire; États-Unis -- Relations extérieures.; URSS -- Relations extérieures.; Impérialisme -- Histoire; Guerre froide; HISTORY -- State & Local -- General; Diplomatic relations; Imperialism; Russia (Federation); Soviet Union; United States; History